Multifaceted ceramic analysis in the study of political expansion: Insights from the Zhou expansion in Shandong, China - Yitzchak Jaffe; Andrew Womack; Karine Taché; Mitya Kletzerman; Nimrod Marom; Ron Palzur; Bo Sun; Yichao Zhao (Proceedings of the National Academy of Sciences, 2026)
This paper demonstrates the importance of applying multiple analytical methods in ceramic analysis for understanding colonial contact in the past. We examine the Shang–Zhou transition (circa 1000 BCE) by investigating community-specific uses of li tripod cooking vessels at multiple sites in Shandong Province. Craft traditions and food practices serve as valuable proxies for understanding past social identities and offer new perspectives on culture contact, migration, and colonialism. Moving away from ethnicity and political control reflected in ceramic form and style, we focus on how these vessels were made and used. By combining petrography, use-alteration analysis, and residue analysis, we provide an integrated multimethod approach that enables us to reconstruct intersecting levels of social practice through a single ubiquitous artifact. Petrographic analysis reveals how and where vessels were made; use-alteration analysis shows how they were used to cook food; and residue analysis identifies what foods were prepared. By tracing production and consumption traditions before, during, and after Zhou expansion, we show that change in our multivariate dataset resist unidimensional ascription to the Shang–Zhou transition, and hence to unequal outcomes from its impacts.